Adsorption of nucleotides onto ferromagnesian phyllosilicates: Significance for the origin of life. (1st March 2016) - Pedreira-Segade, Ulysse; Feuillie, Cécile; Pelletier, Manuel; Michot, Laurent J.; Daniel, Isabelle
Abstract: The concentration of prebiotic organic building blocks may have promoted the formation of biopolymers in the environment of the early Earth. We therefore studied the adsorption of RNA monomers AMP, GMP, CMP, and UMP, and DNA monomers dGMP, dCMP, and TMP, on minerals that were abundant in the early Earth environment as the result of aqueous or hydrothermal alteration of the primitive oceanic crust. We focused our study on swelling clays, i.e. nontronite and montmorillonite, and non-swelling phyllosilicates, i.e. pyrophyllite, chlorite, lizardite and chrysotile suspended in an aqueous saline solution analog to seawater. In this reference study, adsorption experiments were carried out under standard conditions of pressure and temperature and controlled pH. Under such conditions, this work is also relevant to the preservation of nucleic acids in Fe–Mg-rich terrestrial and Martian soils. We compared the adsorption of the different monomers on individual minerals, as well as the adsorption of single monomers on the whole suite of minerals. We found that DNA monomers adsorb much more strongly than RNA monomers, and that any monomer containing the G nucleobase adsorbed more strongly than one containing the C nucleobase. At high surface loadings (greater than about 1 mM monomer in aqueous solution) we also found a dramatic increase in the slope of adsorption isotherm on the swelling clays, leading to large increases in the amounts adsorbed. Data were processed in order to understand the adsorption mechanism of nucleotides onto mineral surfaces. We infer that all nucleotides behave as homologous molecules in regard to their adsorption onto the studied mineral surfaces. At low to moderate surface loadings, their adsorption is best explained by a single mechanism common to the suite of minerals of the present study. At pH 7, adsorption certainly proceeds by ligand exchange between the phosphate group and the hydroxyls of the broken edges of phyllosilicates leading to the saturation of lateral surfaces. Below pH 4, swelling clays also adsorb nucleotides through cation exchange on basal surfaces, whereas non-swelling phyllosilicates do not. However, at high surface loadings an additional mechanism stabilizing adsorption occurs. Given the proposed adsorption mechanisms, the possibility of a favorable polymerization at the mineral–water interface is discussed. We propose that Fe–Mg rich phyllosilicates tightly bind nucleotides, under ambient conditions, and concentrate them up to 1000 times the solution concentration upon saturation. Nontronites have the most diverse and favorable adsorption behaviors and could have helped to the concentration and polymerization of nucleotides under primitive Earth-like conditions.